Disease Stage-Associated Alterations in Learning and Memory through the Electroacupuncture Modulation of the Cortical Microglial M1/M2 Polarization in Mice with Alzheimer’s Disease - Long Li; Le Li; Jiayong Zhang; Sheng Huang; Weilin Liu; Zhifu Wang; Shengxiang Liang; Jing Tao; Lidian Chen (Neural Plasticity)
Microglia are the primary cells that exert immune function in the central nervous system, and accumulating evidence suggests that microglia act as critical players in the initiation of neurodegenerative disorders, such as Alzheimer’s disease (AD). Microglia seemingly demonstrate two contradictory phenotypes in response to different microenvironmental cues, the M1 phenotype and the M2 phenotype, which are detrimental and beneficial to pathogenesis, respectively. Inhibiting the M1 phenotype with simultaneous promoting the M2 phenotype has been suggested as a potential therapeutic approach for cure AD. In this study, we demonstrated that electroacupuncture at the Shenting and Baihui acupoints for 16 weeks could improve learning and memory in the Morris water maze test and reduce amyloid β-protein in the parietal association cortex and entorhinal cortex in mice with mild and moderate AD. Besides, electroacupuncture at the Shenting and Baihui acupoints not only suppressed M1 marker (iNOS/IL-1β) expression but also increased the M2 marker (CD206/Arg1) expression in those regions. We propose that electroacupuncture at the Shenting and Baihui acupoints could regulate microglial polarization and decrease Aβ plaques to improve learning and memory in mild AD mice.